A cycle of brain gain, waste and drain - a qualitative study of non-Eu migrant doctors in Ireland - THOMAS, STEPHEN; TYRRELL, ELLA; NORMAND, CHARLES (My University, 2013)
Background Ireland is heavily reliant on non-EU migrant health workers to staff its health system. Shortages of locally trained health workers and policies which facilitate health worker migration have contributed to this trend. This paper provides insight into the experiences of non-EU migrant doctors in the Irish health workforce. Method In-depth interviews were conducted with 37 non-EU migrant doctors in Ireland in 2011/2012. Results Respondents believed they had been recruited to fill junior hospital doctor ‘service’ posts. These posts are unpopular with locally trained doctors due to the limited career progression they provide. Respondents felt that their hopes for career progression and postgraduate training in Ireland had gone unrealised and that they were becoming de-skilled. As a result, most respondents were actively considering onward migration from Ireland. Discussion & conclusions Failure to align the expectations of non-EU migrant doctors with the requirements of the health system has resulted in considerable frustration and a cycle of brain gain, waste and drain. The underlying reasons for high mobility into and out of the Irish medical workforce must be addressed if this cycle is to be broken. The heavy reliance on non-EU migrant doctors to staff the medical workforce has distracted from the underlying workforce challenges facing the Irish medical workforce.
PUBLISHED
Keywords: Doctor migration; Medical workforce planning; Health workforce planning; Human resources for health; International Integration